Profil Farmakokinetik dan Ketersediaan Hayati Tiga Sediaan Tablet Natrium Diklofenak Salut Enterik - Yeyet Cahyati Sumirtapura; Herwanto Suhalim; Weda Wibawati (Institut Teknologi Bandung, 1997)
Pharmacokinetic and bioavailability studies of three enteric coated 50-mg sodium diclofenac tablets marketed in Indonesia (DR-50, FR-50 and VN-50) have been carried out in six healthy Indonesian volunteers with three-way crossover design. The results obtained showed that there were significant differences in the bioavailability parameters of the three products tested. The lag-time observed varied from 1 to 2 hours for DR-50, 0.5 to 2 hours for FR-50, and 1.5-2 hours for VN-50. Peak plasma levels of 1.16 + 0.59, 2.06 + 1.03, and 0.68 + 0.3 Î¼g/ml were reached in 3.3 + 1.4, 1.9 + 0.9, and 3.8 + 1.2 hours following administration of DR-50, FR-50 and VN-50, respectively. The area under the curve given by each product were 3.81 + 1.60 Î¼g/ml.hr for DR-50, 3.87 + 0.89 Î¼g/ml.hr.for FR-50, and 3.13 + 1.33 Î¼g/ml.hr for VN-50. The elimination half life of diclofenac observed varied from 2.1 to 6.9 hours with a mean value of 3.7 + 1.5 hours.